Electrical tunable topological valley photonic crystals for on-chip optical communications in the telecom band - Qi, Zhipeng (2023)
On-chip optical communications are in increasingly demand for low-loss, small-footprint and power-efficient waveguiding solutions in the telecom band. However, most integrated optical circuits suffer from high propagation loss and low integration degree. Through manipulating the valley-dependent topological phase of light, we have experimentally demonstrated both robust optical transport and electrical modulation of lightwaves at telecom wavelengths in the valley photonic crystals. With the adoption of valley kink states, the 25 Gbit/s optical signal at 1550 nm is successfully transmitted through a highly twisted interface. Furthermore, an extreme high data rate of 100 Gbit/s is demonstrated with such topological waveguide by wavelength division multiplexing. The electrical tunability of the topological modulators based on thermo-optic effect is also verified, opening a novel route towards active valley kink photonic devices. Our study shows a great possibility of making use of the topological protection in building up high-speed datalinks on a chip.